2015
DOI: 10.3390/md13042233
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Chemical Analysis of the Lipopolysaccharide from Aeromonas hydrophila Strain AH-1 (Serotype O11)

Abstract: A group of virulent Aeromonas hydrophila, A. sobria, and A. veronii biovar sobria strains isolated from humans and fish have been described; these strains classified to serotype O11 are serologically related by their lipopolysaccharide (LPS) O-antigen (O-polysaccharide), and the presence of an S-layer consisting of multiple copies of a crystalline surface array protein with a molecular weight of 52 kDa in the form of a crystalline surface array which lies peripheral to the cell wall. A. hydrophila strain AH-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…7), some conserved functional properties clearly emerge. The carbohydrate backbones of the OPS from K. pneumoniae O12 and Aeromonas hydrophila AH-1 are identical, although AH-1 OPS also possesses variable acetylation at the 2 and 3 positions of the Rhap residue (38). The OPS-biosynthesis genetic locus of AH-1 contains a putative acetyltransferase gene.…”
Section: Discussionmentioning
confidence: 96%
“…7), some conserved functional properties clearly emerge. The carbohydrate backbones of the OPS from K. pneumoniae O12 and Aeromonas hydrophila AH-1 are identical, although AH-1 OPS also possesses variable acetylation at the 2 and 3 positions of the Rhap residue (38). The OPS-biosynthesis genetic locus of AH-1 contains a putative acetyltransferase gene.…”
Section: Discussionmentioning
confidence: 96%
“…In a number of L-Rha-containing OPSs, synthesis of adaptor is catalysed by rhamnosyltransferase WbbL, which transfers a single L-Rha residue to DGlcNAc-PP-Und (Rubires et al, 1997;Mills et al, 2004). Predicted rhamnosyltransferase Orf5 shares 21 % identity and 38 % similarity to WbbL of Aeromonas hydrophila O1 (Merino et al, 2015) and, thus, may fulfil this function in F. pulveris G3872. However, a role of Orf5 in the formation of a rhamnosidic linkage within the repetitive OPS domain rather than in the adaptor cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported that FKC vaccine applied to tilapia broodstock gave RPS value 78.26% on day five to the offspring after challenged with A. hydrophila (Sukenda et al, 2017), while lipopolysaccharides were a molecular constituent of Gram-negative bacterial outer membranes that are toxic to fish, making the bacteria become virulent. This molecule is amphiphilic and composed of oligosaccharides, polysaccharides, O-antigen, and lipid-A in the form of acetylglucosamine phosphate fatty acid (Merino et al, 2015). LPS in bacteria are able to provide an immunomodulatory effect on the host (Dehghani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%